2022
DOI: 10.1002/aac2.12057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surgery on the survival of elderly patients with early stage pancreatic cancer: A propensity‐matched analysis

Abstract: Background and objectives Research about the effect of surgery in geriatric patients with early stage pancreatic ductal adenocarcinoma (PDAC) is limited, and it remains a subject of much debate. The purpose of this study was to evaluate the role of surgery on the survival of elderly patients with T1‐3N0M0 PDAC and to further investigate the prognosis of these patients undergoing different surgical methods. Methods Patients aged ≥65 with T1‐3N0M0 PDAC diagnosed in 2004–2016 were collected from the Surveillance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Several retrospective analyses have evaluated the value of adjuvant chemotherapy in the subset of elderly patients. The latest retrospective cohort research led by Mehtsun et al has found that receipt of adjuvant chemotherapy Hilal et al [51] Retrospective 524 Young: 64 ( Lu et al [52] Retrospective 4283 Young: 64 ( Wu et al [53] Retrospective Satoi et al [55] Retrospective 556 ≥80 2007-2014 Pancreatectomy vs chemotherapy, palliative therapy OS 22.8 vs 18.5 0.64 (0.44-0.93) .020…”
Section: Safety Feasibility and Effect Of Chemotherapy In Elderly Pda...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several retrospective analyses have evaluated the value of adjuvant chemotherapy in the subset of elderly patients. The latest retrospective cohort research led by Mehtsun et al has found that receipt of adjuvant chemotherapy Hilal et al [51] Retrospective 524 Young: 64 ( Lu et al [52] Retrospective 4283 Young: 64 ( Wu et al [53] Retrospective Satoi et al [55] Retrospective 556 ≥80 2007-2014 Pancreatectomy vs chemotherapy, palliative therapy OS 22.8 vs 18.5 0.64 (0.44-0.93) .020…”
Section: Safety Feasibility and Effect Of Chemotherapy In Elderly Pda...mentioning
confidence: 99%
“…[52] Besides, a retrospective cohort analysis based on the Surveillance, Epidemiology, and End Results (SEER) database indicated that surgical intervention could provide a survival benefit to elderly patients with early-stage PDAC (stages I–IIA) and these elderly patients could benefit from more radical operations. [53] One study by Ikenaga et al also showed there were no apparent differences in morbidity, mortality, or postoperative hospital stay between the young (≤79) and the elderly (≥80), however, the elderly underwent PD for PDAC, had shorter overall survival (OS) than those aged ≤79 years. [54] Additionally, Satoi et al have carried out a largest-scale multi-center retrospective study including 365 octogenarians in the surgery group and 99 octogenarians in the chemotherapy group, which clearly revealed a favorable prognosis in the surgery group (with median survival time: 20.6 months) relative to the chemotherapy group (with median survival time: 18.6 months) in the elderly.…”
Section: Clinical Management In Elderly Pdac Patientsmentioning
confidence: 99%